2022
DOI: 10.1155/2022/1663330
|View full text |Cite
|
Sign up to set email alerts
|

Macrofilaricidal Activity, Acute and Biochemical Effects of Three Lichen Species Found on Mount Cameroon

Abstract: Onchocerciasis is a parasitic infection affecting a relatively small population globally but has very devastating pathological outcomes. Ivermectin and recently moxidectin are the only drugs approved for clinical management of the disease, both of which have several limitations. In particular, they are efficacious against microfilariae (microfilaricidal) with no activity against adult worms (nonmacrofilaricidal). Promising anthelmintic activity has been reported in some lichens. This study investigated three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, the AST: ALT ratios were high for both extracts suggesting severe liver injury. Other studies have reported high AST: ALT ratios with significant histopathological changes in the liver tissue of treated animals, but no mortality was recorded suggesting possible reversible liver injury [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the AST: ALT ratios were high for both extracts suggesting severe liver injury. Other studies have reported high AST: ALT ratios with significant histopathological changes in the liver tissue of treated animals, but no mortality was recorded suggesting possible reversible liver injury [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%